Peran Keluarga Dalam Memberikan Dukungan Sosial Pada Lansia Penderita Stroke Klien “E” - R.A Siti Khairunisa; Suryati suryati; Hartika Utami Fitri (Social Science and Contemporary Issues Journal, 2023)
This thesis is entitled "The Role of Family in Providing Social Support for Elderly Stroke Patients, Client 'E'." The research focuses on the family's role in providing social support for elderly stroke patients, encompassing the actions of family members in offering assistance, the types of support provided, and the challenges faced. The purpose of this study is to comprehend the family's role in providing social support to the elderly, the types of support given, and the arising obstacles. This research employs a qualitative approach with field research methodology. The research subjects consist of five family members who care for elderly stroke patients. Data is collected through interviews and documentation.The research findings demonstrate that the family's role in providing social support for elderly stroke patients is highly significant. Social support has a positive impact on these elderly individuals, boosting their spirits, reducing despair, and managing the clients' emotions. The social support rendered includes emotional support, tangible support, and instrumental support. However, several obstacles are also identified, including the elderly's difficulties in controlling their emotions and unfulfilled promises from busy family members. In conclusion, families play a vital role in providing social support for elderly stroke patients. This support has a positive impact on the psychological and emotional aspects of the elderly. Nonetheless, specific challenges need to be considered in the effort to provide effective social support.